Vascular and neural mechanisms of ACh-mediated vasodilation in the forearm cutaneous microcirculation - Berghoff, Martin; Kathpal, Madeera; Kilo, Sonja; Hilz, Max J; Freeman, Roy (Journal of applied physiology (1985), 2002)
The relative contribution of endothelial vasodilating factors to acetylcholine (ACh)-mediated vasodilation in the forearm cutaneous microcirculation is unclear. The aims of this study were to investigate the contributions of prostanoids and cutaneous C fibers to basal cutaneous blood flow (CuBF) and ACh-mediated vasodilation. ACh was iontophoresed into the forearm, and cutaneous perfusion was measured by laser-Doppler flowmetry. To inhibit the production of prostanoids, four doses of acetylsalicylic acid (ASA; 81, 648, 972, and 1,944 mg) were administered orally. Cutaneous nerve fibers were blocked with topical anesthesia. Cyclooxygenase inhibition did not change basal CuBF or endothelium-mediated vasodilation to ACh. In contrast, ASA (972 and 1,944 mg) significantly reduced the C-fiber-mediated axon reflex in a dose-dependent fashion. Blockade of C-fiber function significantly reduced axon reflex-mediated vasodilation but did not affect basal CuBF or endothelium-dependent vasodilation. The findings suggest that prostanoids do not contribute significantly to basal CuBF or endothelium-dependent vasodilation in the forearm microcirculation. In contrast, prostanoids are mediators of the ACh-provoked axon reflex.